Attention deficit hyperactivity disorder: genetic association study in a cohort of Spanish children. Issue 1 (December 2015) - Gomez-Sanchez, Clara; Riveiro-Alvarez, Rosa; Soto-Insuga, Victor; Rodrigo, Maria; Tirado-Requero, Pilar; Mahillo-Fernandez, Ignacio; Abad-Santos, Francisco; Carballo, Juan; Dal-Ré, Rafael; Ayuso, Carmen
Abstract Background Attention deficit hyperactivity disorder (ADHD) has a strong genetic component. The study is aimed to test the association of 34 polymorphisms with ADHD symptomatology considering the role of clinical subtypes and sex in a Spanish population. Methods A cohort of ADHD 290 patients and 340 controls aged 6–18 years were included in a case–control study, stratified by sex and ADHD subtype. Multivariate logistic regression was used to detect the combined effects of multiple variants. Results After correcting for multiple testing, we found several significant associations between the polymorphisms and ADHD (p value corrected ≤0.05): (1)SLC6A4 andLPHN3 were associated in the total population; (2)SLC6A2, SLC6A3, SLC6A4 andLPHN3 were associated in the combined subtype; and (3)LPHN3 was associated in the male sample. Multivariable logistic regression was used to estimate the influence of these variables for the total sample, combined and inattentive subtype, female and male sample, revealing that these factors contributed to 8.5, 14.6, 2.6, 16.5 and 8.5 % of the variance respectively. Conclusions We report evidence of the genetic contribution of common variants to the ADHD phenotype in four genes, with theLPHN3 gene playing a particularly important role. Future studies should investigate the contribution of genetic variants to the risk of ADHD considering their role in specific sex or subtype, as doing so may produce more predictable and robust models.